Pendekatan Hermeneutika Khaled M. Abou el- Fadl untuk Membedakan antara Ajaran Otoritas dan Otoritarianism - Baiq Tuhfatul Unsi (Muróbbî: Jurnal Ilmu Pendidikan, 2018)
Islamic law faces trauma of modernity and colonialism which has an impact on the emergence of authoritarian attitudes in treating texts. Authoritarianism is the act of locking will of God, or will of text in a certain determination, and then presenting that determination as a given, definite, absolute, and decisive. According to the analysis of Khaled M. Abou el-Fadl, this phenomenon, especially about the discourse of Islamic law, is the result of mistakes in taking methodological procedures related to the relationship between author, text and reader. The reader that locks the text in a certain meaning, it has damaged the integrity of the author and text itself. In the dimension of authoritarian interpretation, dominant problem in determining is at reader level. Methodology offered by Khaled is a negotiative hermeneutic, where between three text-author-reader elements must be negotiated, pressure point is more on reader without annulling two other elements. Because for him, reader is always experiencing changes and dynamics throughout his life. In addition, readers also have an interest in text. This is due to human being as reader who gives his voice and meaning to text. Three things are needed to maximize this negotiative hermeneutic performance; competence and text validation, determination of meaning and concept of representation.